Innovation in fintech lending applications, can increase impulsive buying? Designing a research model based on a literature review - Wisnu Yuwono; Juviyanty; Ferdinand Nainggolan (Citakonsultindo, 2025)
Fintech lending applications is currently growing very rapidly, and shows a fairly high risk of default, especially among millennials. Based on these conditions, it is necessary to carry out research related to designing research models that answer research problems related to increasing the use of fintech lending applications among millennials. This research is qualitative using a systematic review theory approach. The data used are research articles that are relevant to the topics discussed by researchers with a total of 50 articles from various research journals. The results of the research recommend a research model with technology acceptance model variables, promotional programs in the form of live streaming promotions and discounts, e-WOM, service reliability, family influence and government influence.